Encapsulation of oxime K027 into cucurbit[7]uril: In vivo evaluation of safety, absorption, brain distribution and reactivation effectiveness - Zdarova Karasova, Jana; Hepnarova, Vendula; Andrys, Rudolf; Lisa, Miroslav; Jost, Petr; Muckova, Lubica; Pejchal, Jaroslav; Herman, David; Jun, Daniel; Kassa, Jiri; Kuca, Kamil (Toxicology letters, 2020)
Oxime-based acetylcholinesterase reactivators (briefly oximes) regenerate organophosphate-inactivated acetylcholinesterase and restore its function. Poor blood-brain-barrier passage and fast elimination from blood limit their actual use in treatment of patients exposed to organophosphates. Previous in vitro results implicated further testing of cucurbit[7]uril as a delivery vehicle for bisquaternary oximes. The present paper focuses on cell toxicity, in vivo safety and influence of cucurbit[7]uril on oxime pharmacokinetics and pharmacodynamics. Neither the K027 nor the complex caused any cell toxicity, changes in blood biochemistry or hepato- or nephrotoxicity in tested concentrations. The encapsulation of K027 increased and accelerated the blood-brain-barrier penetration. The peripheral oxime exposure also increased, supporting the suggestion that cucurbit[7]uril protects the circulating oxime from rapid renal clearance. Contrary to the comparable in vitro reactivation power of K027 and the encapsulated K027, we failed to confirm this in vivo. In theory, this might result from the non-specific binding of molecules to the cucurbit[7]uril or the interaction of K027 with cucurbit[7]uril being too strong for acetylcholinesterase reactivation. Precise explanation requires additional in silico, in vitro and also in vivo experiments.
Keywords: Animals; Maximum Tolerated Dose; Acetylcholinesterase; Hep G2 Cells; cucurbit[7]uril; vztah mezi dávkou a účinkem léčiva; hodnocení rizik; Female; buňky Hep G2; Tissue Distribution; CNS targeting; ženské pohlaví; oximy; Pyridinium Compounds; erytrocyty; Cholinesterase Reactivators; přemostěné cyklické sloučeniny; Mouse; Sarin; pyridinové sloučeniny; GPI-vázané proteiny; lidé; maximální tolerovaná dávka; Injections, Intramuscular; A549 Cells; mozek; injekce intramuskulární; Risk Assessment; Imidazoles; Dose-Response Relationship, Drug; Oximes; CB[7]; Male; Erythrocytes; acetylcholinesterasa; Brain; Bridged-Ring Compounds; reaktivátory cholinesterasy; GPI-Linked Proteins; Oxime K027; Mice, Inbred ICR; tkáňová distribuce; myši inbrední ICR; Cell Survival; zvířata; mužské pohlaví; viabilita buněk; buňky A549; imidazoly; Humans